Physiological attributes of banana and plantain cultivars of the Colombian Musaceae Collection (2015)
The Colombian Musaceae Collection (CMC) contains 140 banana and plantain cultivars. For this study, twelve cultivars were selected when they were in the initial flowering stage and the physiological attributes of the plants and some components of the bunches were studied. Similar cultivar groups were determined in terms of the evaluated attributes with the use of a multivariate statistical analysis for principal components and grouping analysis. With 89.35% explanation of the total variance by the first five components, the variables fresh weight of the bunches, fresh weight of the fruit, number of fruits, specific leaf area, total dry weight of the plant, dry weight of the corms, and percentage of dry weight of the bunches represented the majority of the differentiation of the cultivars. This study allowed for the evaluation and comparison of the principal promising banana and plantain cultivars for use as basic tools in selection programs of the Musaceae germplasm in terms of agronomic and productive behaviors.